Culture and low level of class oral participation in speaking activities of students from intensive advanced l courses at the departament of Foreign Language Department of the University of El Salvador during the year 2014 - Montano Parada, Patricia Lorena autor
In the last decades, the English Language has become the language which people put on their interest to learn as much as possible. To learn this language brings along to students the possibilities to increase many opportunities in their professional life. To learn this language represents to learn and to develop all the macro skills in order to communicate the message in the best way. So, the active participation in the language learning process results into the fundamental aspect to accomplish the requirements along the major. In this case, the research points out the problematic that occurs in students of Advanced English I course at the FLD at the University of El Salvador where students show a low level oral participation in speaking activities during the class. Along this line, a body of research has investigated factors that influence students‟ inactive verbal participation in classrooms, such as culture, language proficiency, and affective aspects (Adamson, 1990; Chen, 2003; Jones, 1999; Kim, 2006; Liu, 2001, 2005; Morita, 2000, 2004; Tsui, 1996). Whereby, this research is focused in the influence that culture has over low level oral participation in class. “These factors include whether the reticence results from students‟ negative attitudes towards English as a medium of communication (Liu &Littlewood, 1997), students‟ lack of language proficiency (Cheng, 2000; Kim, 2006), students‟ identity differences, including cultural characteristics (Jones, 1999; Morita, 2000; 2004), and students‟ different perceptions of classroom participation” (Chen, 2003; Chu & Kim, 1999; Inoue, 1999; Jackson, 2002; Kim, 2006; Liu, 2001, 2005).